Effect of lead factors on the embrittlement of RPV SA-508 cl 3 steel - Kempf, Rodolfo (2013)
This paper presents a project to study the effect of lead factors on the mechanical behaviour of the SA-508 type 3 Reactor Pressure Vessel (RPV) steel used in the reactor under construction Atucha II in Argentina. Charpy-V notch specimens of this steel were irradiated at the RA1 experimental reactor at a temperature of 275 C with two lead factors (186 and 93). The neutron flux was 3.71 1015 n m2 s1 and 1.85 1015 n m2 s1 (E > 1 MeV) respectively. In both cases, the fluence was 6.6 1021 n m2 , which is equivalent to that received by the PHWR Atucha II RPV in 10 years of full power irradiation. The results of Charpy tests revealed significant embrittlement both in the DT = 14 C and DT = 21 C shifts of the ductile–brittle transition temperatures (DBTT) and in the reduction of the maximum energy absorbed. This result shows that the shift of the DBTT with a lead factor of 93 is larger than that obtained with a lead factor of 186. Then, the results of irradiation in experimental reactors (MTR) with high lead factors may not be conservative with respect to the actual RPV embrittlement.